Design of new power generating circuit for passive UHF RFID tag - Abdelali El Boutahiri; Mounir Ouremchi; Ahmed Rahali; Mustapha El Alaoui; Fouad Farah; Karim El khadiri; Ahmed Tahiri; Hassan Qjidaa (Institute of Advanced Engineering and Science, 2019)
In this paper, we propose a new power generating circuit for passive ultra high frequency (UHF) RFID tag. The proposed power generating circuit consists of a RF limiter, a high power efficiency and high sensitivity full wave radio frequency (RF) wave rectifier and a low-power regulator with NMOS diodes work like a DC-limiter. The design method proposed in this study use one low drop out (LDO) regulator to provide tow output stable supply voltages vdd1 of value 1V for the digital section supply, and vdd2 of value 0.5V for the analog front-end section power supply. The proposed power generating circuit is optimized in terms of power consumption of RFID tag system to have a high operating range under conditions of 50 Ohm antenna, -24 dBm input RF power, 900MHz and 1 M DC, with low power dissipation and 29.15% large power conversion efficiency. The power generating circuit was designed, simulated and layouted in Cadence using TSMC 180 nm technology. The final design occupies approximately 0.25mm2.